Bicuspid Aortic Valve and Thoracic Aortic Aneurysm: Three Patient Populations, Two Disease Phenotypes, and One Shared Genotype - Robert B. Hinton (Cardiology Research and Practice)
Bicuspid aortic valve (BAV) and thoracic aortic aneurysm (TAA) are two discrete cardiovascular phenotypes characterized by latent progressive disease states. There is a clear association between BAV and TAA; however the nature and extent of this relationship is unclear. There are both distinct and overlapping developmental pathways that have been established to contribute to the formation of the aortic valve and the aortic root, and the mature anatomy of these different tissue types is intimately intertwined. Likewise, human genetics studies have established apparently separate and common contributions to these clinical phenotypes, suggesting complex inheritance and a shared genetic basis and translating 3 patient populations, namely, BAV, TAA, or both, into a common but diverse etiology. A better understanding of the BAV-TAA association will provide an opportunity to leverage molecular information to modify clinical care through more sophisticated diagnostic testing, improved counseling, and ultimately new pharmacologic therapies.